Erratum: Dependence of the black-body force on spacetime geometry and topology. (31st July 2017) - Muniz, C. R.; Maciel, G.; Cunha, M. S.; Landim, R. R.; Costa Filho, R. N.
Abstract: Original article: EPL, 117 (2017) 60001 .